2007
DOI: 10.1590/s0074-02762007005000019
|View full text |Cite
|
Sign up to set email alerts
|

Astrovirus infection in children living in the Central West region of Brazil

Abstract: This study presents data regarding the circulation of astrovirus in Goiânia-GO and Brasília-DF. These viruses were detected in fecal samples from hospitalized children up to five years old with and without acute gastroenteritis. A total of 1244 fecal samples were collected in two periods, 1994 to 1996 (Brasília) and 1998, and were analyzed for viral RNA using the reverse transcription-polymerase chain reaction (RT-PCR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
2
11
3
Order By: Relevance
“…This circulation pattern corroborates the seasonality data obtained from other studies in the region, which have shown higher incidence rates for astroviruses and caliciviruses during periods with elevated relative air humidity 19,20 . The focus on public health and preventive measures (even when treatment is not available) has given greater visibility to pregnant women (whether HIV-seropositive or not), because of the greater vulnerability of their immune system 10 .…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This circulation pattern corroborates the seasonality data obtained from other studies in the region, which have shown higher incidence rates for astroviruses and caliciviruses during periods with elevated relative air humidity 19,20 . The focus on public health and preventive measures (even when treatment is not available) has given greater visibility to pregnant women (whether HIV-seropositive or not), because of the greater vulnerability of their immune system 10 .…”
Section: Resultssupporting
confidence: 91%
“…In a more recent study, Silva et al detected genotype 1 in 42.8% of the positive samples, followed by genotype 2 (23.2%) and genotype 4 (14.3%) 14 . Santos et al reported similar astrovirus detection rates (3%) among children less than five years of age who were hospitalized due to acute gastroenteritis in Goiânia and Brasília (7%) 19 . In another study, Andreasi et al 4 reported a detection rate of 3.1% for astrovirus, among children in Campo Grande (MS), and found that out of the total of 10 samples, six belonged to serotype 1…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…In Brazil, recent studies have described astrovirus detection rates as varying from 3.4-28.2% (Gabbay et al 2007, Resque et al 2007, Santos et al 2007, Victoria et al 2007.…”
mentioning
confidence: 99%